Use of programme budgeting and marginal analysis to set priorities for local NHS dental services: learning from the north east of England. (3rd May 2018) - Holmes, R D; Steele, J G; Exley, C; Vernazza, C R; Donaldson, C
Abstract: Background: Priority setting is necessary where competing demands exceed the finite resources available. The aim of the study was to develop and test a prioritization framework based upon programme budgeting and marginal analysis (PBMA) as a tool to assist National Health Service (NHS) commissioners in their management of resources for local NHS dental services. Methods: Twenty-seven stakeholders (5 dentists, 8 commissioners and 14 patients) participated in a case-study based in a former NHS commissioning organization in the north of England. Stakeholders modified local decision-making criteria and applied them to a number of different scenarios. Results: The majority of financial resources for NHS dental services in the commissioning organization studied were allocated to primary care dental practitioners' contracts in perpetuity, potentially constraining commissioners' abilities to shift resources. Compiling the programme budget was successful, but organizational flux and difficulties engaging local NHS commissioners significantly impacted upon the marginal analysis phase. Conclusions: NHS dental practitioners' contracts resemble budget-silos which do not facilitate local resource reallocation. 'Context-specific' factors significantly challenged the successful implementation and impact of PBMA. A local PBMA champion embedded within commissioning organizations should be considered. Participants found visual depiction of the cost-value ratio helpful during their initial priority setting deliberations.